T5 exonuclease hydrolysis of Hepatitis B Virus replicative intermediates allows reliable quantification and fast drug efficacy testing of covalently closed circular DNA by PCR - Qu, Bingqian; Ni, Yi; Lempp, Florian A.; Urban, Stephan (Journal of virology, 2018)
Chronic infection with the human hepatitis B virus (HBV) is a major health problem. Virus persistence requires the establishment and maintenance of covalently closed circular DNA (cccDNA), the episomal virus template in the nucleus of infected hepatocytes. Compared to replicative DNA intermediates (relaxed circular DNA [rcDNA]), copy numbers of cccDNA in infected hepatocytes are low. Accordingly, accurate analyses of cccDNA require enrichment of nuclear fractions and Southern blotting or selective quantitative PCR (qPCR) methods allowing discrimination of cccDNA and rcDNA. In this report, we analyzed cccDNA-specific primer pairs for their ability to amplify cccDNA selectively. Using mixtures of defined forms of HBV and genomic DNA, we determined the potential of different nucleases for targeted digestion of the open/relaxed circular DNA forms in the absence and presence of genomic DNA without affecting cccDNA. We found that the combination of T5 exonuclease with a primer set amplifying an approximately 1-kb fragment permits reliable quantification of cccDNA without the requirement of prior nucleus enrichment or Hirt extraction. We tested this method in four different in vitro infection systems and quantified cccDNA copy numbers at increasing multiplicities of inoculated genome equivalents. We further analyzed the kinetics of cccDNA formation and the effect of drugs (interferon, entry inhibitors, and capsid inhibitors) on cccDNA. Our method allows reliable cccDNA quantification at early stages of infection in the presence of a high excess of input virus and replicative intermediates and is thereby suitable for drug screening and investigation of cccDNA formation and maintenance. - IMPORTANCE cccDNA elimination is a major goal in future curative regimens for chronic HBV patients. However, PCR-based assays for cccDNA quantification show a principally constrained specificity when high levels of input virus or replicative intermediates are present. Here, we characterized T5 exonuclease as a suitable enzyme for medium-throughput in vitro assays that preserves cccDNA but efficiently removes rcDNA prior to PCR-based quantification. We compared T5 exonuclease with the previously described exonuclease III and showed that both nucleases are suitable for reliable quantification of cccDNA by PCR. We substantiated the applicability of our method through examination of early cccDNA formation and stable accumulation in several in vitro infection models and analyzed cccDNA stability after administration of anti-HBV drugs. Our results support the use of T5 exonuclease for fast and convenient rcDNA removal, especially for early cccDNA quantification and rapid drug testing in in vitro studies.
Accepted manuscript posted online: 19 September 2018
Gesehen am 18.05.2020